Synthesis of Biolubricant via Chemical Modification from Vegetable Oil Blend using Heterogeneous Catalyst - Rajwani, S.; Yadav, P.K.S. (Asian Journal of Chemistry, 2021)
Present study reports the synthesis of biolubricant synthesis from the vegetable oil blend [dehydrated castor oil (DCO) and waste ricebran oil (WRBO)] using heterogeneous catalyst and its physico-chemical properties. The biolubricant was synthesized from blend of vegetable oils using two chemical modification processes i.e. synthesizing methyl esters of blend oil using sodium methoxide as catalyst and then epoxidation of synthesized methyl esters using Amberlite IR-120 strongly acidic ion-exchange resin. The biolubricant sample was examined by 1H & 13C NMR and FT-IR analysis. Viscosity index, rheological properties, thermal stability and pour point values of chemical and structurally modified blend oil (i.e. biolubricant) (Tonset = 215 ºC, iodine value (IV) = 197.5, pour point (PP) = -4.5 ºC) showed notable improvement than that from blend oil methyl esters (Tonset = 181 ºC, iodine value (IV) = 167.65, pour point (PP) = -9.5 ºC). Thus, a blend of non-edible oil (dehydrated castor oil) and waste cooking oil (WRBO) is likely to be used potentially as biolubricant basestock for hydraulic applications.